2021
DOI: 10.1007/s00520-021-06168-y
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of hair recovery after (neo)adjuvant chemotherapy with scalp cooling in Japanese breast cancer patients

Abstract: Purpose Scalp cooling during chemotherapy infusion to mitigate alopecia for breast cancer patients is becoming widespread; however, studies regarding hair recovery after chemotherapy with scalp cooling are limited. We conducted a prospective study of hair recovery after chemotherapy with scalp cooling. Patients and methods One hundred and seventeen Japanese female breast cancer patients who completed planned (neo)adjuvant chemotherapy using the Paxman Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
3
4
0
1
Order By: Relevance
“…However, the most important influence is the chemotherapeutic agent. In accordance with previously published studies [ 9 , [12] , [13] , [14] ], we observed that SC was more effective in patients receiving taxane monotherapy than in patients receiving an anthracycline-taxane-based regimen. Using the patients’ evaluation, 50% of patients with taxane monotherapy had grade 1 alopecia compared to 17.2% of patients with an anthracycline-taxane-based regimen.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, the most important influence is the chemotherapeutic agent. In accordance with previously published studies [ 9 , [12] , [13] , [14] ], we observed that SC was more effective in patients receiving taxane monotherapy than in patients receiving an anthracycline-taxane-based regimen. Using the patients’ evaluation, 50% of patients with taxane monotherapy had grade 1 alopecia compared to 17.2% of patients with an anthracycline-taxane-based regimen.…”
Section: Discussionsupporting
confidence: 93%
“…The subjective patient self-evaluation may be influenced by the medical education on SC that patients received, knowing that hair loss was more likely to happen in an anthracycline-taxane-based regimen. The primary reason for discontinuation of SC was hair loss, which is consistent with other studies where hair loss was also the main reason for SC discontinuation [ 7 , 12 , 25 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Aktuell ist das Scalp Cooling (SC) eine vielversprechende Methode, um CIA zu verhindern 3 4 5 6 . Diesbezüglich gibt es bereits zahlreiche Veröffentlichungen, jedoch wurde der Einfluss der Kopfhautkühlung auf das Regrowth erst in wenigen Publikationen beschrieben 1 3 7 . Ziel der Hair-Safe Studie war es neben der Effektivität des SC im klinischen Alltag auch den Einfluss des SC auf das Regrowth der Haare nach CIA zu analysieren.…”
unclassified